1995
DOI: 10.1104/pp.108.2.727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Calcium on Short-Term NO3- Fluxes in Roots of Barley Seedlings

Abstract: The effect of pH and Ca2+ on net NO,-uptake, influx, and efflux by intact roots of barley (Hordeum vulgare 1.) seedlings was studied. Seedlings were induced with NO,-or NO,-. Net NO,-uptake and efflux, respectively, were determined by following its depletion from, and accumulation in, the external solution. Since roots of both uninduced and NO,--induced seedlings contain little internal NO3-, initial net uptake rates are equivalent to influx (M. Aslam NO3-uptake (influx) by these roots was little affected at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…− uptake is depressed under alkaline conditions (Aslam et al, 1995). Magnesium functions in metabolic processes of plants.…”
Section: Nomentioning
confidence: 99%
“…− uptake is depressed under alkaline conditions (Aslam et al, 1995). Magnesium functions in metabolic processes of plants.…”
Section: Nomentioning
confidence: 99%
“…These authors suggested that the net rate of nitrate transport from vacuole to cytoplasm was proportional to the vacuolar nitrate concentration and that remobilisation followed ®rst-order kinetics. However, it has also been suggested that nitrate accumulated in the vacuole is not readily available or is not remobilised fast enough to sustain plant assimilation requirements during times of nitrogen de®ciency (Aslam et al 1976;Rufty et al 1982;Morgan et al 1985;Oscarson and Larsson 1986).…”
Section: Introductionmentioning
confidence: 98%
“…Isso foi comprovado também por SOUSA et al (2002) MURATA et al, 2003). As paredes celulares em crescimento se estendem mais rapidamente em pH ácido do que em pH neutro por um fenômeno conhecido como crescimento ácido (TAIZ & ZEIGER, 2004) e tal efeito é atenuado na presença de cálcio (ASLAM et al, 1995).…”
Section: Resultsunclassified